COVID-19-Related Pleural Diseases - Iqbal, Beenish; Rahman, Najib M.; Hallifax, Rob J. (Seminars in Respiratory and Critical Care Medicine, 2023)
Coronavirus disease 2019 (COVID-19)-related pleural diseases are now well recognized. Since the beginning of the pandemic, increasing cases of pleural diseases including pneumothorax, pneumomediastinum, and pleural effusion with severe COVID-19 infection have attracted the attention of physicians and are not incidental or due to barotrauma. The complicated course of COVID-19 illness highlights the complex pathophysiological underpinnings of pleural complications. The management of patients with pneumothorax and pneumomediastinum is challenging as the majority require assisted ventilation; physicians therefore appear to have a low threshold to intervene. Conversely, pleural effusion cases, although sharing some similar patient characteristics with pneumothorax and pneumomediastinum, are in general managed more conservatively. The evidence suggests that patients with COVID-19-related pleural diseases, either due to air leak or effusion, have more severe disease with a worse prognosis. This implies that prompt recognition of these complications and targeted management are key to improve outcomes.
Keywords: COVID-19; pleural diseases; pneumothorax; pneumomediastinum; pleural effusion; complications